PENDEKATAN INTERAKSIONAL DAN TEORITIS DALAM KAJIAN VIKTIMOLOGI - Servasius T. Seran; Melkhior Romualdus Yofa Efo; Nikolaus Jeri Alexander Leto; Dwityas Witarti Rabawati (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Interactional and theoretical approaches in victimology complement each other to provide a holistic understanding of victimisation. The interactional approach highlights individual dynamics, while the theoretical approach explores structural and psychological factors. Through the integration of both, victimology can continue to develop as a relevant field of science to effectively combat crime and protect victims.